Dmp53, Basket and drICE Gene Knockdown and Polyphenol Gallic Acid Increase Life Span and Locomotor Activity in a Drosophila Parkinson’s Disease Model (2013)
ABSTRACT: Understanding the mechanism(s) by which dopaminergic (DAergic) neurons are eroded in Parkinson's disease (PD) is critical for effective therapeutic strategies. By using the binary tyrosine hydroxylase (TH)-Gal4/UAS-X RNAi Drosophila melanogaster system, we report that Dmp53, basket and drICE gene knockdown in dopaminergic neurons prolong life span (p < 0.05; log-rank test) and locomotor activity (p < 0.05; χ(2) test) in D. melanogaster lines chronically exposed to (1 mM) paraquat (PQ, oxidative stress (OS) generator) compared to untreated transgenic fly lines. Likewise, knockdown flies displayed higher climbing performance than control flies. Amazingly, gallic acid (GA) significantly protected DAergic neurons, ameliorated life span, and climbing abilities in knockdown fly lines treated with PQ compared to flies treated with PQ only. Therefore, silencing specific gene(s) involved in neuronal death might constitute an excellent tool to study the response of DAergic neurons to OS stimuli. We propose that a therapy with antioxidants and selectively "switching off" death genes in DAergic neurons could provide a means for pre-clinical PD individuals to significantly ameliorate their disease condition.